PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Maria Stefania Waro Bheri; Suwignyo Widagdo; Lia Rachmawati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2021)
This study aims to determine the effect of Good Corporate Governance consisting of the number of independent commissioners, the number of the board of directors, the number of audit committees on the company's performance in banking companies listed on the IDX. The population in this study are banking companies listed on the Indonesia Stock Exchange as many as 46 banking companies in Indonesia that are listed or go public. The sample in this study were 10 banking companies with four years of financial statements from 2017 – 2020 listed on the IDX. The sampling technique used is purposive sampling. Data collection uses secondary data taken from www.idx.co.id. The analysis technique used is multiple linear regression analysis. The results of the research data show that Good Corporate Governance which consists of the number of independent commissioners, the number of the board of directors, the number of audit committees together has a positive and significant effect on company performance in banking companies. The results of the significance test partially state that the number of independent commissioners has a negative effect, the number of boards of directors has a positive effect, while the number of audit committees has no effect on company performance.